Sonority as a Phonological Cue in Early Perception of Written Syllables in French - Tossonian, Méghane; Ferrand, Ludovic; Lucas, Ophélie; Berthon, Mickaël; Maïonchi-Pino, Norbert (Frontiers in Psychology, 2020)
Many studies focused on the letter and sound co-occurrences to account for the well-documented syllable-based effects in French in visual (pseudo)word processing. Although these language-specific statistical properties are crucial, recent data suggest that studies that go all-in on phonological and orthographic regularities may be misguided in interpreting how—and why—readers locate syllable boundaries and segment clusters. Indeed, syllable-based effects could depend on more abstract, universal phonological constraints that rule and govern how letter and sound occur and co-occur, and readers could be sensitive to sonority—a universal phonological element—for processing (pseudo)words. Here, we investigate whether French adult skilled readers rely on universal phonological sonority-related markedness continuum across the syllable boundaries for segmentation (e.g., from marked, illegal intervocalic clusters /zl/ to unmarked, legal intervocalic clusters /lz/). To address this question, we ran two tasks with 128 French adult skilled readers using two versions of the illusory conjunction paradigm (Task 1 without white noise; Task 2 with white noise). Our results show that syllable location and segmentation in reading is early and automatically modulated by phonological sonority-related markedness in the absence or quasi-absence of statistical information and does not require acoustic-phonetic information. We discuss our results toward the overlooked role of phonological universals and the over-trusted role of statistical information during reading processes.